Culture-bound syndromes in popular culture
1 online resource.
Keywords: "This volume explores culture-bound syndromes, defined as a pattern of symptoms (mental, physical, and/or relational) experienced only by members of a specific cultural group and recognized as a disorder by members of those groups, and their coverage in popular culture. Encompassing a wide range of popular culture genres and mediums - from film and TV to literature, graphic novels and anime - the chapters offer a dynamic mix of approaches to analyze how popular culture has engaged with specific culture-bound syndromes such as hwabyung, hikikomori, taijin kyofusho, zou huo ru mo, sati, amok, Cuban hysteria, voodoo death, and others. Spanning a global and interdisciplinary remit, this first-of-its-kind anthology will allow scholars and students of popular culture, media and film studies, comparative literature, medical humanities, cultural psychiatry and philosophy to explore simultaneously a diversity of popular cultures and culturally rooted mental health disorders"--